Part of the Job: The positive side of office politics - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2012)
It may sound counter intuitive but playing with office politics may not necessary make you the villain at work. Embracing office politics and learning to use it positively can help companies retain talent and build ethical leadership, says Jane Horan author of a new book I Wish I’d Known That Earlier In My Career: The Power of Positive Workplace Politics